1993
DOI: 10.1002/j.1552-4604.1993.tb03940.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pharmacokinetics and Tolerability of Tirilazad Mesylate, a 21‐Aminosteroid Free Radical Scavenger: I. Single‐Dose Administration

Abstract: The single-dose tolerability and pharmacokinetics of tirilazad mesylate, a 21-aminosteroid free radical scavenger, were assessed in 47 healthy male subjects. Subjects were randomized to receive citrate vehicle (n = 12) or 0.25 mg/kg (n = 9), 0.5 mg/kg (n = 9), 1.0 mg/kg (n = 8), or 2.0 mg/kg (n = 9) tirilazad mesylate by 0.5-hour intravenous infusion. Injection site pain was observed with approximately equal frequency in both vehicle and tirilazad mesylate treatment groups. No statistically significant effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Clinical trials studying the tolerability and pharmacokinetics of lazaroids have been reported [29][30][31]. In one such study, using U-74600F (tirilazad mesylate, a lazaroid compound), Fleishaker et al found that doses of up to 10 mg/kg/day given every 6 h for 5-10 days are tolerable in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials studying the tolerability and pharmacokinetics of lazaroids have been reported [29][30][31]. In one such study, using U-74600F (tirilazad mesylate, a lazaroid compound), Fleishaker et al found that doses of up to 10 mg/kg/day given every 6 h for 5-10 days are tolerable in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Because the mean half-life of tirilazad mesylate is relatively long (3.7 h for healthy male volunteers [32]), lazaroid reduced reperfusion injury after 3-h warm ischemia when administered as a bolus infusion of 10 mg/kg before ischemia.…”
Section: Original Researchmentioning
confidence: 99%
“…No satisfactory biochemical explanation for toxicity exists. In particular, although tirilazad is a steroid, it has not been found to exhibit glucocorticoid activity in humans 15,16 or to affect the pituitary adrenocortical axis in rats. 41 Hence, it is unlikely that tirilazad worsened outcome through glucocorticoid effects, although it remains unclear what effects corticosteroids have in acute ischemic stroke.…”
mentioning
confidence: 97%
“…However, tirilazad had variable effects on neurological outcome in transient forebrain ischemia in the rat. 13,14 Phase I results in normal, healthy, human volunteers found that single and multiple intravenous doses of up 12 mg/kg tirilazad were well tolerated [15][16][17] ; local infusion-related irritation and thrombophlebitis were the main adverse events, partially explained by the presence of citrate in the vehicle solution. 16 Tirilazad did not alter cerebral blood flow or its reactivity to carbon dioxide or cerebral oxygen metabolism in normal subjects.…”
mentioning
confidence: 99%